2007
DOI: 10.1115/1.2768109
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Convective Alveolar Flow Induced by Rhythmic Breathing Motion of the Pulmonary Acinus

Abstract: Low Reynolds number flows (Re<1) in the human pulmonary acinus are often difficult to assess due to the submillimeter dimensions and accessibility of the region. In the present computational study, we simulated three-dimensional alveolar flows in an alveolated duct at each generation of the pulmonary acinar tree using recent morphometric data. Rhythmic lung expansion and contraction motion was modeled using moving wall boundary conditions to simulate realistic sedentary tidal breathing. The resulting alveolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 26 publications
11
78
0
Order By: Relevance
“…3). Hence, alveolar flow patterns are determined by the interplay between shear flow over alveolar mouths, leading to recirculation, and radial streamlines induced by wall motion, as noted previously [6][7][8]15]. As one travels towards regions where the strength of the ductal flow decreases, recirculation regions disappear and fluid fills alveolar cavities in a radial fashion ( fig.…”
Section: Alveolar Flow Patternsmentioning
confidence: 90%
See 1 more Smart Citation
“…3). Hence, alveolar flow patterns are determined by the interplay between shear flow over alveolar mouths, leading to recirculation, and radial streamlines induced by wall motion, as noted previously [6][7][8]15]. As one travels towards regions where the strength of the ductal flow decreases, recirculation regions disappear and fluid fills alveolar cavities in a radial fashion ( fig.…”
Section: Alveolar Flow Patternsmentioning
confidence: 90%
“…For this, we increased the density of volume elements by approximately 30% above the value that was eventually used (~540'000 elements). To achieve sufficiently accurate results such that changes in the resulting entrance flow Re were within <5% upon further time step refinement, a time step of ∆t=T/200 was eventually implemented [15]. Lagrangian trajectories of fluid (or massless) particles,…”
Section: Methodsmentioning
confidence: 99%
“…The continuity equation represents the conservation of mass, Equation (1), and the Navier-Stokes equations represent the conservation of momentum, Equation (2), that would be solved numerically on a moving grid using a commercial finite-volume based …”
Section: Governing Equationsmentioning
confidence: 99%
“…They concluded that the ratio of duct volume to cavity volume would be an effective parameter of flow patterns in alveolar sacs. Sznitman et al [2] considered rhythmic breathing motion of the pulmonary acinus and simulated induced air flow through the model of the alveolated ducts at each generation of the pulmonary acinar tree. They demonstrated the importance of three dimensional (3D) simulations in investigating existing complex flow patterns in alveolar sacs.…”
Section: Introductionmentioning
confidence: 99%
“…Several collaborators used the extracted datasets for simulating the airflow [143,144] and particle deposition [145] in the terminal airways.…”
Section: Finite Element Reconstruction Of the Terminal Airwaysmentioning
confidence: 99%